1979
DOI: 10.1085/jgp.74.1.71
|View full text |Cite
|
Sign up to set email alerts
|

The effect of strychnine, bicuculline, and picrotoxin on X and Y cells in the cat retina.

Abstract: A B S T a A C T The effect of intravenous strychnine and the GABA antagonists picrotoxin and bicuculline upon the discharge pattern of center-surround-organized cat retinal ganglion cells of X and Y type were studied. Stimuli (mosdy scotopic, and some photopic) were selected such that responses from both on and off-center cells were either due to the center, due to the surround, or clearly mixed. Pre-drug control responses were obtained, and their behavior following administration of the antagonists was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

1982
1982
1994
1994

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 40 publications
3
18
1
Order By: Relevance
“…The concentration in the retina itself must have been lower due to the blood-retinal barrier. These doses are slightly below those calculated by Caldwell, Daw & Wyatt (1978) for their experiments on -rabbits, and are the same as those which have previously been shown to be effective on cat retinal ganglion cells (Kirby & Enroth-Cugell, 1976;Kirby, 1979).…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…The concentration in the retina itself must have been lower due to the blood-retinal barrier. These doses are slightly below those calculated by Caldwell, Daw & Wyatt (1978) for their experiments on -rabbits, and are the same as those which have previously been shown to be effective on cat retinal ganglion cells (Kirby & Enroth-Cugell, 1976;Kirby, 1979).…”
Section: Introductionsupporting
confidence: 74%
“…Under scotopic conditions pictrotoxin affected the linear receptive field components of Y cells (Kirby & Enroth-Cugell, 1976;, while under the mesopic and photopic conditions used here its major effect was on the non-linear responses. Strychnine also has quite different effects under the two conditions, reducing centre sensitivity under mesopic but not scotopic conditions (Kirby, 1979). Differences in pharmacology might be expected on the basis of the differences in the rod and cone pathways at the level of the inner plexiform layer (Kolb & Famiglietti, 1974;Nelson, Famiglietti & Kolb, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…The results from studies using intravenous injection of GABA and bicuculline indicate a difference between X-and Y-type retinal ganglion cells (Kirby & Enroth-Cugell, 1976;Kirby, 1979;Kirby & Schweitzer-Tong, 1981). X cells seem to be unaffected by GABA and its antagonists, Y cells show a difference in the centre surround organization and in the centre size when bicuculline or picrotoxin are injected.…”
Section: Conclusion From Gaba Localizationmentioning
confidence: 99%
“…Later studies on ganglion cells in the cat retina reported more specific effects of systemically applied strychnine. Chu (1968) found that the inhibition of off-centre but not of on-centre ganglion cells was blocked by strychnine, whereas Kirby (1979) found effects of strychnine only on brisk-sustained(X) cells but not on brisk-transient(Y) cells, irrespective of whether the cells were on-or off-centre ganglion cells. Using an isolated eyecup preparation Saito (1981) reported that the surround inhibition of on-centre brisk-sustained(X) cells was blocked by strychnine, whereas the surround inhibition of other ganglion cell types was unaffected by strychnine.…”
Section: Introductionmentioning
confidence: 99%